Mineral trapping of a CO2/H2S mixture by hematite under initially dry hydrothermal conditions. (August 2016) - Alpermann, Theodor; Dietrich, Marcel; Ostertag-Henning, Christian
Graphical abstract: Highlights: Dissolution of hematite by a "dry" supercritical CO2 /H2 S mixture. Formation of an aqueous phase in an initially dry mineral-gas system. Coupled mineral trapping of H2 S and CO2 by hematite. Reactions in dried-out zone in underground CO2 /H2 S storage. Abstract: For the experimental simulation of geochemical processes occurring in the vicinity of an injection well for CO2 with H2 S impurities, the reaction of hematite with a CO2 /H2 S acid gas mixture in an initially water-free system was investigated. At the reaction conditions (120 °C, 12 MPa), a reductive dissolution of hematite and the successive precipitation of iron sulfide minerals pyrrhotite, marcasite and pyrite together with siderite were observed within days. Precipitation of secondary minerals presumably occurred either in the supercritical CO2 phase or, more likely, in an aqueous phase generated during the reaction progress due to the high initial H2 S portion in CO2 . The overall process can be described by Fe2 O3 + 2H2 S + CO2 → FeS2 + FeCO3 + 2H2 O. The observed process is relevant for the geologic co-storage of CO2 with H2 S in sandstone formations with a substantial fraction of hematite (e.g. red-beds). There, mineral trapping of CO2 will be significantly promoted by reaction of co-injected H2 S or SO2 with hematite – even in the dried-out zone near the injection well. This process can significantly impact the porosity of the storage rock due to an initial dissolution of hematite and subsequent deposition of secondary minerals with larger total volume. Hence, a plugging of pore throats appears to be feasible even in the desiccated zone in the vicinity of a CO2 or acid gas injection well.